2020
DOI: 10.1038/s41594-020-00520-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure, lipid scrambling activity and role in autophagosome formation of ATG9A

Abstract: De novo formation of the double-membrane compartment autophagosome is seeded by small vesicles carrying membrane protein autophagy-related 9 (ATG9), whose function remains unknown. Here we find that ATG9A scrambles phospholipids of membranes in vitro. Cryo-EM structures of human ATG9A reveal a trimer with a solvated central pore, which is connected laterally to the cytosol through the cavity within each protomer. Similarities to ABC exporters suggest that ATG9A could be a transporter that uses the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
252
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(257 citation statements)
references
References 78 publications
5
252
0
Order By: Relevance
“…Under physiological conditions, autophagy activity is required to maintain the homeostasis of the system. For example, autophagy related 9 (ATG 9), the sole transmembrane protein, mediates lipid scrambling and plays a crucial role in the lipid transport system that enables phagophore expansion [7,8]. Additionally, ATG 16L1 contributes to cell survival in the nutrient depletion state [9].…”
Section: Autophagy and The Lysosomementioning
confidence: 99%
“…Under physiological conditions, autophagy activity is required to maintain the homeostasis of the system. For example, autophagy related 9 (ATG 9), the sole transmembrane protein, mediates lipid scrambling and plays a crucial role in the lipid transport system that enables phagophore expansion [7,8]. Additionally, ATG 16L1 contributes to cell survival in the nutrient depletion state [9].…”
Section: Autophagy and The Lysosomementioning
confidence: 99%
“…ATG9A vesicles are mobile, and their trafficking is controlled via nutrient-regulated signals ( Young et al, 2006 ). Previous studies have found the importance of ATG9A during autophagosome formation, proposedly by functioning in vesicular delivery to the phagophore initiation site, and by translocating lipids from the outer to the inner phagophore membrane in order to enable its expansion ( Maeda et al, 2020 ; Matoba et al, 2020 ; Orsi et al, 2012 ). Upon starvation-induced autophagy, ATG9A redistributes from the perinuclear Golgi regions to an enrichment juxtaposed to the autophagosome initiation site ( Judith et al, 2019 ; Lamb et al, 2016 ; Longatti et al, 2012 ; Young et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are required in order to recruit the only membrane-spanning ATG protein, ATG9A, to the pre-autophagosomal structure and forming phagophore ( Funderburk et al, 2010 ; Takahashi et al, 2011 ). ATG9A and its yeast counterpart were recently shown to have lipid scramblase activity, thereby translocating phospholipids between the two monolayers of lipid bilayers, presumably in order to drive expansion of the nascent autophagosome membrane ( Maeda et al, 2020 ; Matoba et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It facilitates autophagosomal membrane expansion acting as a scramblase. Specifically, ATG9 transports phospholipids from the cytoplasmic to the luminal leaflet of the isolation membrane [ 18 , 19 , 20 , 21 , 22 ]. ESCRT (endosomal sorting complexes required for transport) machinery facilitates phagophore closure, a process involving membrane fission of the inner and outer membrane at the phagophore edge [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%